2004
DOI: 10.1186/1471-2105-5-128
|View full text |Cite
|
Sign up to set email alerts
|

DIALIGN P: Fast pair-wise and multiple sequence alignment using parallel processors

Abstract: Background: Parallel computing is frequently used to speed up computationally expensive tasks in Bioinformatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, both approaches fail completely when sequences have no characters in common. New approaches that are a hybrid of alignment methods, an increasingly active research area, are appropriate for data with mixed fragment and genome information (Schmollinger et al, 2004; Subramanian et al, 2005; Liu et al, 2012; Hossain et al, 2013; Ye et al, 2015; Nguyen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, both approaches fail completely when sequences have no characters in common. New approaches that are a hybrid of alignment methods, an increasingly active research area, are appropriate for data with mixed fragment and genome information (Schmollinger et al, 2004; Subramanian et al, 2005; Liu et al, 2012; Hossain et al, 2013; Ye et al, 2015; Nguyen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…DIALIGN was selected because it has many applications in comparative genomics [68]. Also, a recent benchmark study for the alignment of non-coding DNA sequences has concluded that it can produce alignments with high sensitivity as well as specificity to detect constrained sites [69].…”
Section: Methodsmentioning
confidence: 99%
“…When a pair-wise tool is used, the algorithms need to handle permutations, substitutions (with many different matrices depending on the kind of analysis to be performed), deletions and gaps. Moreover, most of the pair-wise algorithms (not the heuristic version) are related to Smith-Waterman and Needleman-Wunsch (two dynamic programming algorithms) and are not efficient on large sequences [38]. Since the presence of sequence patterns seems to be the exception rather than the rule, but assuming that some regularity must govern the lipid-peptide interactions, we considered an alternative paradigm called "alignment-free": this paradigm avoids some problems related to pair-wise analysis [37].…”
Section: Introductionmentioning
confidence: 99%